Brexpiprazole–catechol cocrystal: structure elucidation, excipient compatibility and stability. Issue 44 (30th October 2019) - Arabiani, Mohsin R.; K, Bal Raju; Bhunia, Surojit; Teja, Pyla Kranthi; Lodagekar, Anurag; Chavan, Rahul B.; Shastri, Nalini R.; Reddy, C. Malla; Shelat, Pragna; Dave, Divyang
Abstract : Cocrystallization improved the stability of the brexpiprazole. Abstract : Brexpiprazole (BREX) is a well known drug used in the treatment of atypical psychotic disorder. BREX is known to exhibit photo-instability on granulation with the most commonly used binder, polyvinylpyrrolidone (PVP), in wet granulation. The present study reports a cocrystal of BREX with catechol (CAT), its structure elucidation using single crystal X-ray diffraction and its processability. The brexpiprazole–catechol (BRC) cocrystal crystallizes in the P 21 / c space group. Structural analysis of BRC shows R22(8) between BREX and CAT through weak C–H⋯O and strong O–H⋯O hydrogen bond interactions. BREX is marketed in tablet dosage form. The compatibility of the generated cocrystal in the presence of several excipients was evaluated using differential scanning calorimetry (DSC) and powder X-ray diffraction (PXRD). The cocrystal remained stable, with no signs of incompatibility during the excipient compatibility study. Additionally, the cocrystal and plain BREX granulated with PVP as a binder and the chemical stability of the granules were investigated. Plain BREX showed oxidative degradation and formation of N -oxide degradation products under stability conditions within 7 days. More importantly, the BRC cocrystal displayed superior stability against stability conditions because the reactive site in the piperazine ring of the BREX moiety was blocked in the BRC cocrystal due to the hydrogen bond between the drug and co-former.